Nexus Between Financial Development, FDI, Globalization, Energy Consumption and Environment: Evidence From BRI Countries - Lu, Jie; Imran, Muhammad; Haseeb, Abdul; Saud, Shah; Wu, Mengyun; Siddiqui, Faiza; Khan, Muhammad Jalal (Frontiers in Energy Research, 2021)
The aim of this study is to explore the nexus between foreign direct investment, financial development, energy consumption, economic growth and globalization for selected panel of belt and road initiative (BRI) countries over the period of 1990-2017. After employing appropriate panel unit root tests, the Westerlund co-integration test, DSUR long-run panel estimation approach and the Dumitrescu-Hurlin panel causality test, the results reveal the presence of significant long-run nexus among the analyzed variables. The DSUR results shows that energy consumption boost by 0.023% and 0.790% when there is a 1% rise in foreign direct investment and economic growth occurs. Whereas, 1% increase in financial development and globalization reduce energy consumption by 0.049% and 0.621% respectively. We also found bidirectional relationships of energy consumption with financial development, and foreign direct investment with globalization for selected sample of our study. On the other hand, a unidirectional causal relationship exists running from energy consumption towards both financial development and foreign direct investment. Increase in FDI including energy-efficient technology, development of financial sector leads to sustainable economic growth of these countries. The finding reveals the need to formulate energy policies that promotes energy efficiency among Belt and Road Initiative (BRI) countries.